Assumptions of Naming in Information Storage and Retrieval: A Deconstruction - Olson, Hope A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Naming information is the special business of librarians and information professionals. Our theories, models and descriptions, applied in our role as intermediaries between users and information , are as presumptuous as scientists' construction and containment of nature. As we decide what descriptors and other access points to use we affect access to and the use of information.